FDI and onshore task composition: Evidence from German firms with affiliates in the Czech Republic - Konstantin Koerner; Mathilde Le Moigne (Journal for Labour Market Research, 2023)
How does a firm's foreign direct investment (FDI) in a low-wage country change its onshore task demand in a high-wage country? Is the shift more intensive for jobs that the literature has designated offshorable? We address these questions using a matched difference-in-differences (DiD) approach with data on German firms that have similar propensities to conduct FDI in the Czech Republic. Our novel matching procedure draws on post-lasso logit estimates and shows that high task intensities of managing, administration, and labor legislation play a major role in firms' engagement in international expansion. The outcomes of the DiD estimation show that after acquiring a foreign affiliate, multinational enterprises (MNEs) increase the intensities of their activities typical of headquarters such as managing, analyzing, and negotiating relative to the corresponding task intensities among non-MNEs. We also find sector-specific decreases, such as a reduction in typical production tasks (monitoring, producing, measuring) in manufacturing MNEs or typical service tasks (informing, medical, repairing) in service MNEs.
Keywords: F16; F66; J24; 330; FDI; Tasks; Trade; Ofshorability; Central and Eastern Europe; Germany